Tingkat Penerimaan Konsumen Terhadap Abon Daging Dan Tulang Ikan Layang (Decapterus ruselli) - Fien Sudirjo; Ismael Marasabessy; Anggeline Amahorseja; Kristhina Rahael; Dani Royani (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Decapterus is one of the demersal fish that is cheap and quite abundant. Making shredded fish using glider meat has been widely done but there is no information about making shredded fish using Decapterus bones. This study aims to utilize shredded meat and bones in making shredded, to determine the yield of shredded meat and shredded swallow bones and determine the level of consumer acceptance of shredded swallowfish meat and shredded Decapterus bones produced. The ingredients used are fresh Decapterus from the Langgur traditional fish market. Additional ingredients in the form of spices are onion, garlic, ginger, galangal, lemongrass, turmeric, coriander, cumin, pepper, flavoring, white sugar, salt, tamarind, bay leaf, orange leaf and coconut milk. The research will be conducted in January 2023 at the Fish Processing Laboratory and Organoleptic Testing Laboratory, Tual State Fisheries Polytechnic. The results show that Decapterus can be used as an ingredient in making shredded, both from meat and bones. The shredded yield of Decapterus meat is 48.05% while the yield of shredded Decapterus bone is 69.26%. The level of consumer acceptance of shredded Decapterus meat and shredded Decapterus bone is for the parameters of smell, taste and texture are not significantly different, while for the parameters of color and appearance are significantly different.